Electrosprayed crispr plasmid DNA loaded alginate nanoparticles : preparation, characterisation, and gene editing - Alallam, Batoul (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2021)
Background: CRISPR/ Cas9 is one of the most powerful among the approaches being developed to rescue fundamental causes of gene-based inheritable diseases. Several strategies for delivering such genome editing materials have been developed, but the safety, efficacy over time, cost of production, and gene size limitations are still under debate and must be addressed to further improve applications. Sodium alginate is frequently used as the model encapsulation matrix for bioactive ingredients in the field of drug and gene delivery due to its safety. Objective: To encapsulate CRISPR/Cas9 plasmid DNA in alginate nanocarrier to perform genome editing. Methodology: alginate nanoparticles loaded with two CRISPR pDNA were fabricated using electrospray method. Both formulation and process were optimised. Chitosan-, Arabic gum- and PEG-coated CRISPR-loaded alginate nanoparticles were fabricated and characterised. CRISPR-loaded alginate nanoparticles physicochemical properties were compared to the surface-modified nanoparticle properties. The influence of surface modification of nanoparticles on their interaction with cell was studied in regard to cellular uptake, cytotoxicity, transfection efficiency, and genome editing. Results: Using electrospray, a nanoparticle carrier was developed to deliver CRISPR pDNA into HepG2 cells. The nanoparticles size was approximately 230 nm, with an encapsulation efficiency of 99%. Release study revealed that over one-third of the pDNA was released within the first 24 h. In vitro experiments conducted with HepG2 cells demonstrated that after 48 h of treatment with the CRISPR-loaded alginate nanoparticles, the particles were not toxic. CRISPR-loaded alginate nanoparticles mediated 1.5-folds more efficient transfection than a commercially available cationic liposome-based transfection reagent. However, their indel efficiency was 3.4-folds lower than the transfection reagent. The surface coating highly affected the nanoparticles physicochemical properties, consequently, their safety and efficiency in delivering the plasmid. CS CRISPR ALG NPs showed mean size and zeta potential of 377 nm and 33.67 mV, respectively. Over 90% encapsulation efficiency was achieved while protection payload from serum. The tests revealed that the nanoparticles were cytocompatible and successfully introduced the Cas9 transgene in HepG2 cells. CS CRISPR ALG NPs-transfected HepG2 was able to edit its target plasmid by introducing double-strand break (DSB) in GFP gene, 18.26-folds higher than CRISPR ALG NPs. Conclusions: In this work, plasmids for the CRISPR/Cas9 system were encapsulated in alginate nanoparticles and were shown to induce expression of Cas9 and perform a genome editing in HepG2 cells in vitro. Chitosan-coated CRISPR-loaded alginate nanoparticles revealed the best results with high plasmid protection, sustained release and high indel efficiency. These results suggest that this nanoparticle-based plasmid delivery method can be effective for future in vivo applications of the CRISPR/Cas9 system.